2017
DOI: 10.1186/s13223-017-0213-x
|View full text |Cite|
|
Sign up to set email alerts
|

Passive blood anaphylaxis: subcutaneous immunoglobulins are a cause of ongoing passive anaphylactic reaction

Abstract: BackgroundAllergic, especially anaphylactic, reactions during immunoglobulin replacement therapy are rare, but their pathophysiology and classification remain ambiguous. Recent findings show positive results of skin tests with commercially available immunoglobulins, but target antigens and responsible compounds of the tested immunoglobulins have not been strictly identified.Case description and findingsFour adult patients with recently diagnosed common variable immunodeficiency qualified for standard subcutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Anaphylactic reactions to subcutaneous immunoglobulin preparations are extraordinarily rare and have only been associated with late‐onset allergic reactions. Zdziarski et al reported 4 patients with common variable immune deficiency who presented allergic reactions attributable to IgE or IgG content in the subcutaneous immunoglobulin batch 1 . We present the case of a patient who developed reproducible symptoms compatible with anaphylaxis because of acute‐onset multisystem involvement (skin, respiratory, and gastrointestinal).…”
Section: Figurementioning
confidence: 87%
See 2 more Smart Citations
“…Anaphylactic reactions to subcutaneous immunoglobulin preparations are extraordinarily rare and have only been associated with late‐onset allergic reactions. Zdziarski et al reported 4 patients with common variable immune deficiency who presented allergic reactions attributable to IgE or IgG content in the subcutaneous immunoglobulin batch 1 . We present the case of a patient who developed reproducible symptoms compatible with anaphylaxis because of acute‐onset multisystem involvement (skin, respiratory, and gastrointestinal).…”
Section: Figurementioning
confidence: 87%
“…Lina Maria Castano-Jaramillo, MD 1 , Carla Toledo-Salinas, MD 1 , Edwin Pardo-Diaz, MD 1 , Francisco Alberto Contreras-Verduzco, MD 2 , and David Alejandro Mendoza-Hernandez, MD 2 We present the case of a 12-year-old male with a medical history of severe combined immunodeficiency who underwent hematopoietic stem cell transplantation from a haploidentical related donor and remained dependent on replacement immunoglobulin therapy. He was receiving subcutaneous immunoglobulin at home (Subglobin) for the past 3 years.…”
Section: Anaphylaxis To Subcutaneous Immunoglobulin In a Severe Combined Immunodeficiency Patientmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon publication of the original article [ 1 ], the authors reported the following funding information was omitted: Publication supported by Wroclaw Centre of Biotechnology, programme The Leading National Research Centre (KNOW) for years 2014–2018.…”
Section: Correction To: Allergy Asthma Clin Immunol (2017) 13:41 101mentioning
confidence: 99%
“…The specific IgG shows an increase about four weeks after infection and lasts for the long term, years sometimes, and could be used as a biomarker for the evaluation of recovery [ 9 , 10 ]. In addition, the Igs are always involved in hypersensitivity of the body [ 11 , 12 ]. For example, IgE can induce type I hypersensitivity, and specific IgEs are detected for the determination of allergens.…”
Section: Introductionmentioning
confidence: 99%